The Improve High School Student’s Computational Thinking Ability And Mathematical Resilience with Project Based Learning Assisted By GeoGebra - Martin Valerian Amadeus Saragih; Nurjanah Nurjanah; Kartika Yulianti (Edumatica: Jurnal Pendidikan Matematika)
This study attempts to enhance high school learners' computational thinking and mathematical resilience skills. This study employs quantitative approaches with a quasi-experimental research design, and the type of research is Non-Equivalent Group Design. The tools used in this study were computational thinking skills tests and mathematical resilience questionnaires. From the results of the survey conducted, it is known that: 1) the Project Learning model accompanied by GeoGebra significantly improves computational thinking skills, and Project-Based Learning model has moderate improvement; 2) computational thinking skills of high school students who were taught through Project-Based Learning model aided by GeoGebra improved significantly compared to those taught with the Project-Based Learning model; 3) Project-Based Learning model aided by GeoGebra has a positive effect on the mathematical resilience of high school students, but only to a moderate extent.